ACTG A5353: A Pilot Study of Dolutegravir Plus Lamivudine for Initial Treatment of Human Immunodeficiency Virus-1 (HIV-1)–infected Participants With HIV-1 RNA <500000 Copies/mL. (14th December 2017) - Taiwo, Babafemi O; Zheng, Lu; Stefanescu, Andrei; Nyaku, Amesika; Bezins, Baiba; Wallis, Carole L; Godfrey, Catherine; Sax, Paul E; Acosta, Edward; Haas, David; Smith, Kimberly Y; Sha, Beverly; et al.
Abstract : Dolutegravir plus lamivudine was virologically effective and safe in treatment-naive individuals with human immunodeficiency virus type 1 RNA up to 500 000 copies/mL. A participant who experienced failure developed the M184V lamivudine and the R263R/K integrase resistance mutations. Abstract: Background: Limited data exist on initial human immunodeficiency virus type 1 (HIV-1) treatment with dolutegravir plus lamivudine. Methods: A5353 is a phase 2, single-arm, pilot study of once-daily dolutegravir (50 mg) plus lamivudine (300 mg) in treatment-naive participants with HIV-1 RNA ≥1000 and <500000 copies/mL. Exclusion criteria included active hepatitis B or major protease, reverse transcriptase, or integrase resistance. The primary efficacy measure was the proportion with HIV-1 RNA <50 copies/mL (FDA [US Food and Drug Administration] Snapshot) at week 24. Virologic failure (VF) was confirmed HIV-1 RNA >400 copies/mL at week 16/20 or >200 copies/mL at or after week 24. Dolutegravir levels and drug resistance testing were performed at VF. Results: One hundred and twenty participants (87% male, median age 30 years, 37 (31%) HIV-1 RNA >100000 copies/mL) initiated study treatment. Median entry HIV-1 RNA and CD4 count were 4.61 log10 copies/mL and 387 cells/mm 3 . Virologic efficacy at week 24 was 108/120 (90%, confidence interval [83%, 95%]), with comparable results in the >100000 copies/mL and ≤100000 copies/mL strata, that is, 89% (75%, 97%) and 90% (82%, 96%), respectively. Three participants with VF, had undetected plasma dolutegravir at ≥1 time points; the M184V and R263R/K mutations developed in 1 participant. Two participants experienced grade 3 possible/probable treatment-related adverse events; none discontinued treatment due to adverse events. Conclusions: Dolutegravir plus lamivudine demonstrated efficacy in individuals with pretreatment HIV-1 RNA up to 500000 copies/mL in this pilot trial, but a participant developed resistance mutations. Clinical Trials Registration: NCT02582684.